The church as a trinitarian hermeneutical community - Cho, Anna (HTS teologiese studies, 2024)
This article examines the church as a trinitarian hermeneutical community through the insights of Vanhoozer and the speech act theory. Vanhoozer explained that through the speech act theory, the church should accept the Bible as a communication act of the Triune God and interpret the Triune God in it, and the church should live a life representing the Triune God. This article agrees with his argument, but as there is a point to revise and supplement his discussion from the speech act theory, it re-examines the church as a trinitarian interpretive community. This explains the unification of the epistemological (revelational), ontological and relational perspectives of the Triune God by not separating the immanent Trinity from the economic Trinity. Also, Trinitarianism as a communicator is used to account for the relationship and activity of the Triune God’s perichoresis in the church community and the church in the interpretive community.Contribution: This article engages the church as a trinitarian hermeneutical community of Vanhoozer, and it redeems and reconsiders his argument in the speech act theory. By explaining the communication behaviour of the Trinity and the church, it describes the activities of the Triune God and the appearance of the church, living and working in the church community.